Batasan Prostate Specific Antigen (PSA) pada Pasien Kanker Prostat untuk Memprediksi Metastasis ke Tulang di Rumah Sakit Sardjito, Yogyakarta - AHMAD SULAIMAN LUBIS (National Cancer Center - Dharmais Cancer Hospital, 2014)
The object of this study to establish a serum PSA cut-off value to predict the presence of bone metastasis in prostate cancer. Methods: Consecutive patients diagnosedwith prostate cancer were retrospectively analyzed. Patients had received bone scintigraphy and had their PSA concentration measured. The proper cut-off value was established based on statistical analysis in order to predict the possibility of bone metastasis among them. Results: eighty-three consecutive patients with prostate cancer were enrolled, and 55 patients (66%) with bone metastasis confirmed by scintigraphic findings. A serum PSA concentration of 17.65 ng/ml gave the best sensitivity (78.33%) and specificity (65.21%). The PPV and NPV were 85.45% and 53.57%, respectively (p<0.05) Conclusion: a cut-off value of 17.65 ng/ml appears to be an appropriate benchmark for stratifying metastatic bone disease in prostate cancer patientssuch that if a patient with newly diagnosed prostate cancer and without any skeletal symptoms has a serum PSA concentration of less than 17.65 ng/ml,we suggest that they would not need to undergo bone scintigraphy.